Beliefs about social norms and (the polarization of) COVID-19 vaccination readiness - Silvia Angerer; Daniela Glätzle-Rützler; Philipp Lergetporer; Thomas Rittmannsberger (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2022)
Social norms affect a wide range of behaviors in society. We conducted a representative experiment to study how beliefs about the existing social norm regarding COVID-19 vaccination affect vaccination readiness. Beliefs about the norm are on average downward biased, and widely dispersed. Randomly providing information about the existing descriptive norm succeeds in correcting biased beliefs, thereby reducing belief dispersion. The information has no effect on vaccination readiness on average, which is due to opposite effects among women (positive) and men (negative). Fundamental differences in how women and men process the same information are likely the cause for these contrasting information effects. Control-group vaccination intentions are lower among women than men, so the information reduces polarization by gender. Additionally, the information reduces gendered polarization in policy preferences related to COVID-19 vaccination.
Keywords: C93; D90; I12; 330; social norms; vaccination; COVID-19